1999
DOI: 10.1089/10430349950018094
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Tumor Immunity Elicited by a Recombinant Vaccinia Virus Expressing CD70 (CD27L)

Abstract: CD70, a ligand of the T cell costimulatory receptor CD27, is expressed mainly on activated B cells and has been shown to increase cytotoxic activity and proliferation of preferentially unprimed T cells. Reported herein is the construction of a recombinant vaccinia virus encoding CD70 (designated rV-CD70) and a demonstration of its biological effect on naive T cells in vitro and in vivo. In a whole tumor cell vaccine model, the growth of CD70-negative murine colon adenocarcinoma (MC38) tumor cells infected with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
32
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 28 publications
4
32
0
Order By: Relevance
“…Different protocols in human or murine models have already confirmed this using membrane expressed forms of CD70 molecules. 8,28,29 The results obtained in vitro concerning the inhibition of in vitro tumor proliferation were similar with the two forms of CD70-expressing cells. However, in our models, in vivo experiments showed that tumor rejection by immunocompetent mice is more efficient with CD70-secreting cells than with cells expressing membrane CD70.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Different protocols in human or murine models have already confirmed this using membrane expressed forms of CD70 molecules. 8,28,29 The results obtained in vitro concerning the inhibition of in vitro tumor proliferation were similar with the two forms of CD70-expressing cells. However, in our models, in vivo experiments showed that tumor rejection by immunocompetent mice is more efficient with CD70-secreting cells than with cells expressing membrane CD70.…”
Section: Discussionsupporting
confidence: 65%
“…Experiments carried out in many mice models, with costimulatory molecules, such as CD28, CD40 or CD27 and their respective ligands CD80, CD154 and CD70, have resulted in tumor rejection and generation of antitumor immunity against parental tumor cells. [6][7][8] CD70 is a type II transmembrane glycoprotein, a member of the tumor necrosis factor (TNF) superfamily, which includes CD154 and CD95. 9 Both human and murine T lymphocytes express CD70 and the CD27 ligand.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…20 ± 22 The transfection of CD70 in some immunogenic murine tumor cells have been shown to induce tumor regression and to enhance an antitumor immunity T-cell mediated. 17,23,24 Furthermore, cotransfection of both CD70 and CD80 into the poorly immunogenic MCA 207 tumor cells in the presence of interleukin -12 ( IL-12) has been shown to enhance a protective antitumor immunity against parental tumor growth in a vaccination model. 17 Looking toward the treatment of human cancer, the present study aimed to establish a potent immunotherapy for tumors that lack apparent immunogenicity, and more specifically for such MHC -deficient expression tumor cells.…”
mentioning
confidence: 99%
“…[37][38][39] When employed in vaccination strategies, transgenic expression of CD70 does induce antitumor immunity in solid tumor models. 40,41 In contrast in mice with residual lymphoblastic disease, transgenic expression of CD70 alone is not sufficient to induce an antineoplastic immune response, while the combination of CD70 and IL-2 expressed in vaccine cells affords significant but not complete protection. 42 Therefore, coexpression of CD70 with IL-2 in our current study seemed a highly suitable vaccine combination for the purpose of exploring potentially additive effects mediated by the HSV-1 amplicon vector itself.…”
Section: Hsv-1 Amplicons For Generation Of All Vaccinesmentioning
confidence: 99%